Transformative Islamic Character Education through Project-Based Learning: Promoting Social Responsibility among Muslim Students - Najeeb Yahya; Helene Knudstad; Md. Sultan Mahmud (Ar-rayyan: Journal Of Islamic Education, 2025)
Character education remains one of the primary objectives of Islamic education; however, conventional instructional methods often fail to provide meaningful opportunities for students to practice moral values in authentic social contexts. This study aims to evaluate the effectiveness of Project-Based Learning (PjBL) in promoting transformative Islamic character education and strengthening students' social responsibility. The research adopted a quasi-experimental design involving two comparable classes from Islamic secondary schools. Data were collected using character assessment scales, observation sheets, reflective journals, and interviews. Statistical analysis revealed that students participating in project-based learning achieved significantly higher levels of empathy, cooperation, leadership, responsibility, and civic engagement compared to those receiving conventional instruction. Students also demonstrated increased motivation to implement Islamic values through community service activities and collaborative social projects. The findings suggest that experiential learning provides authentic opportunities for internalizing Islamic moral principles. The novelty of this study lies in integrating Project-Based Learning with Islamic character education into a transformative pedagogical framework that encourages active citizenship and sustainable community engagement